FAKTOR YANG MEMENGARUHI MINAT BERINVESTASI PADA MAHASISWA UNIVERSITAS PGRI MADIUN - Tika Putri Lestari; Liana Vivin Wihartanti; Farida Styaningrum (Bina Ekonomi, 2023)
This study aims to analyze and measure the influence of financial literacy, self-efficacy, social environment, and technological advances on the investment interests of PGRI Madiun University students. The research design used is quantitative research using the explanatory research method. The data source used is primary data. The total population is 210 students, and the sampling technique  used is purposive random sampling using the Slovin formula. The data techniques used in this study are descriptive analysis, instrument testing, classical assumption test, the multiple linear regression test, the t test, and the coefficient of determination test with the help of SPSS software program version 25. These results show that financial literacy, self-efficacy, and technological advances have a significant positive effect on investment interest. While in this study the social environment variable didn’t have a significant positive effect on investment interest.